Longitudinal Radiographic Study of Cranial Bone Growth in Young Cheetah - Steenkamp, Gerhard; Schmidt, Martin J.; van Staden, Paul J.; Bester, Marthàn N. (Frontiers in Veterinary Science, 2019)
Focal palatitis (also known as focal palatine erosion) is thought to be a developmental disease, specifically of cheetah in captivity raised on a commercial diet. The lack of chewing is thought to cause the mandibular molar to change angulation, contacting the palate and causing the lesions. We followed the development of 5 captive cheetah cubs, born within 2 weeks of each other, at the same facility. This longitudinal study followed the cubs cephalometrically from 7 months old to 25 months old. Of each cub we made a lateral and dorsoventral radiograph at 7, 13, 20 and 25 months old. For each radiograph at each age, a predefined series of measurements were made including the angle of the molar. The latter was measured as the angle of the bisecting line running through the apex of the caudal molar root intersecting with a line drawn at the ventral margin of the mandible. The results confirmed that the cheetah skull and neurocranium follows the same neural growth pattern as has been described for other mammalians. Similarly the maxillofacial component follows the same somatic growth as seen in al mammalians excluding humans and non-human primates, where a pubertal growth spurt is present. Finally the angle of the mandibular molar at 7 months differed significantly from the angle at the other ages, however there were no statistical difference in the angulation of the molar after eruption (13 months and older ages). In these five cheetah the lack of chewing (as seen in captivity with a commercial diet) did not alter the angulation of the mandibular molar, nor did the mandibular molars super erupt in these patients at 25 months old.